The effect of exposure duration of self etch dentin bonding on the toxicity of human gingival fibroblast of cell culture - Sri Lestari (Dental Journal (Majalah Kedokteran Gigi), 2008)
Self etch dentin bonding created to make light easily activate the application of composite resin on tooth surface. The monomer content has acid effect that could irritate tooth pulp. The purpose of this study was to evaluate the effect of light exposure duration of self etch dentin bonding on toxicity of human gingival fibroblast of cell culture by MTT assay. Self etch dentin bonding was used as on experimental unit and the sample was exposed by visible light curing in different duration: 10, 20, 30 seconds and immerged in artificial saliva in pH 7 for 24 hours. 100 µl artificial saliva was exposed to human gingival fibroblast of cell culture 20.000 cells/100 µl RPMI for 24 hours. Toxicity was evaluated by MTT assay, optical density was measured using 550 nm spectrophotometer. The data was analyzed using Kruskal Wallis in 5% degree of significance. The result showed that increasing exposure duration (10, 20, 30 seconds) of self etch dentin bonding will reduce the toxicity of human gingival fibroblast of cell culture. It is concluded that 30 seconds-exposure of self etch dentin bonding will reduce the toxicity of human gingival fibroblast of cell culture.